Avaliação do contexto de trabalho na residência multiprofissional em atenção hospitalar à saúde a partir da perspectiva dos residentes - Nascimento, Janequeli Simão (2021)
Multiprofessional Residency in Health is a program created by the Ministry of Health (MH) in conjunction with the Ministry of Education (MEC), and is part of a set of strategies to stimulate the continuing education of health professionals and aims to modify the practices and organization of work in health. The main objective of this research was to describe how multiprofessional residents in hospital health care evaluate the work context through the characterization of the multiprofessional resident profile, the understanding of how non-medical multiprofessional residents perceive the organization, conditions and work relations within the residency program, and the identification of the presence of labor vulnerabilities linked to the performance of the multiprofessional health worker/student resident role. This is a descriptive quantitative study. This research expanded the knowledge about the work context within RESMULTI and identified conditions of precarious professional performance. It also observed that the residency strengthens the policies of permanent and formative education of workers to meet the demands of the SUS and to provide integral care to the population. The multiprofessional health residency is an opportunity that the new graduate has to acquire specific qualification in an area of performance and gain professional experience. The pandemic caused by COVID-19 had wide repercussions in the labor sphere. It caused reconfigurations in the organization of work. And as residents are health workers who needed to act in the "front line" in the fight against the coronavirus in the period 2020-2021, this fact changed the work context of the group studied and produced unexpected repercussions in the production of data, generating impacts on the conduct and development of this research, for this reason, we included a specific subsection to address aspects related to the pandemic.